Your Noise is My Command: Sensing Gestures Using the Body as an Antenna - Cohn, Gabe; Morris, Dan; Patel, Shwetak N.; Tan, Desney (CHI '11 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2011)
Touch sensing and computer vision have made human-computer interaction possible in environments where keyboards, mice, or other handheld implements are not available or desirable. However, the high cost of instrumenting environments limits the ubiquity of these technologies, particularly in home scenarios where cost constraints dominate installation decisions. Fortunately, home environments frequently offer a signal that is unique to locations and objects within the home: electromagnetic noise. In this work, we use the body as a receiving antenna and leverage this noise for gestural interaction. We demonstrate that it is possible to robustly recognize touched locations on an uninstrumented home wall using no specialized sensors. We conduct a series of experiments to explore the capabilities that this new sensing modality may offer. Specifically, we show robust classification of gestures such as the position of discrete touches around light switches, the particular light switch being touched, which appliances are touched, differentiation between hands, as well as continuous proximity of hand to the switch, among others. We close by discussing opportunities, limitations, and future work.